2003
DOI: 10.1128/iai.71.9.5254-5265.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protective Mucosal Th2 Immune Response againstToxoplasma gondiiby Murine Mesenteric Lymph Node Dendritic Cells

Abstract: Toxoplasma gondii, an obligate intracellular parasite pathogen which initially invades the intestinal epithelium before disseminating throughout the body, may cause severe sequelae in fetuses and life-threatening neuropathy in immunocompromised patients. Immune protection is usually thought to be performed through a systemic Th1 response; considering the route of parasite entry it is important to study and characterize the local mucosal immune response to T. gondii. Despite considerable effort, Toxoplasma-targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…The survival time extended up to 15th days (mean of survival = 11.5 days) in ATV vaccinated group and highly significant difference was found between survival curves of ATV vaccinated group and both control groups, these results agreed with the results of Eissa et al (2012) who suggested that significant immune responses were developed following vaccination with ATV as demonstrated by the delayed death of vaccinated mice following RH challenge by nine days. The survival time extended up to 16th days (mean of survival = 12.7 days) in ESA vaccinated group post infection, highly significant difference was found between survival curves of ESA vaccinated group and both control groups, agreeing with extended survival time with ESA up to 15th days reported by Daryani et al (2003).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The survival time extended up to 15th days (mean of survival = 11.5 days) in ATV vaccinated group and highly significant difference was found between survival curves of ATV vaccinated group and both control groups, these results agreed with the results of Eissa et al (2012) who suggested that significant immune responses were developed following vaccination with ATV as demonstrated by the delayed death of vaccinated mice following RH challenge by nine days. The survival time extended up to 16th days (mean of survival = 12.7 days) in ESA vaccinated group post infection, highly significant difference was found between survival curves of ESA vaccinated group and both control groups, agreeing with extended survival time with ESA up to 15th days reported by Daryani et al (2003).…”
Section: Discussionsupporting
confidence: 73%
“…Ali et al (2003) reported decreased pathological changes following vaccination by live cyst vaccines and irradiated cyst vaccine. Even though the tachyzoite challenge was lethal to the mice, it can be concluded that ESA vaccine showed more promising results versus ATV, as demonstrated by the survival rate of vaccinated mice; tachyzoites count and histopathological examination, this could be attributed to the fact that ESA of T. gondii tachyzoites, represent more than 90 % of the parasite circulating antigens, might be the first target of the host immune system (Daryani et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations